Modal Analysis of the High Speed Inner Gear Ring in Planetary Gear Speeder - Liang Yankun; Liu Shijun; Li Zhisheng; Xu Wenbo; Zhou Xusheng (Jixie chuandong)
The Solid Works model of high speed inner gear ring in planetary gear speeder is established,by using the ANSYS Workbench software,the modal analysis of the high speed inner gear ring is carried out,the natural frequency and vibration model are obtained. By the calculation results show that the model can produce resonance in the process of transmission. By improving the design and analysis again,the design can avoid resonance and meet the requirement is found out,the experiments to verify the reasonability of calculation results is carried out.